CHINA IN THE OIL AND GAS BRANCH OF TURKMENISTAN - PARAMONOV, Vladimir; STROKOV, Alexei (CENTRAL ASIA AND THE CAUCASUS, 2015)
In the 1990s, China showed practically no interest in Turkmen oil and gas. It developed this interest in the middle of the first decade of the twenty-first century and has been widening it ever since. In three years (2006-2009), Beijing built up its presence in Turkmenistan and, after the agreements of September 2013, became an uncontested leader in the Turkmen oil and gas industry.